Exopolysaccharide Characterization of Rhizobium favelukesii LPU83 and Its Role in the Symbiosis With Alfalfa - Castellani, Lucas G.; Luchetti, Abril; Nilsson, Juliet F.; Pérez-Giménez, Julieta; Wegener, Caren; Schlüter, Andreas; Pühler, Alfred; Lagares, Antonio; Brom, Susana; Pistorio, Mariano; Niehaus, Karsten; Torres Tejerizo, Gonzalo A. (Frontiers in Plant Science, 2021)
One of the greatest inputs of available nitrogen into the biosphere occurs through the biological N2-fixation to ammonium as result of the symbiosis between rhizobia and leguminous plants. These interactions allow increased crop yields on nitrogen-poor soils. Exopolysaccharides (EPS) are key components for the establishment of an effective symbiosis between alfalfa and Ensifer meliloti, as bacteria that lack EPS are unable to infect the host plants. Rhizobium favelukesii LPU83 is an acid-tolerant rhizobia strain capable of nodulating alfalfa but inefficient to fix nitrogen. Aiming to identify the molecular determinants that allow R. favelukesii to infect plants, we studied its EPS biosynthesis. LPU83 produces an EPS I identical to the one present in Ensifer meliloti, but the organization of the genes involved in its synthesis is different. The main gene cluster needed for the synthesis of EPS I in E. meliloti, is split into three different sections in R. favelukesii, which probably arose by a recent event of horizontal gene transfer. A R. favelukesii strain devoided of all the genes needed for the synthesis of EPS I is still able to infect and nodulate alfalfa, suggesting that attention should be directed to other molecules involved in the development of the symbiosis.